Impact of Timing of Preprocedural Opioids on Adverse Events in Procedural Sedation. (30th January 2020) - Bhatt, Maala; Cheng, Wei; Roback, Mark G.; Johnson, David W.; Taljaard, Monica; ,
Abstract: Background: The risk of respiratory depression is increased when opioids are added to sedative agents. In our recent multicenter emergency department (ED) procedural sedation cohort, we reported a strong association between preprocedural opioids and sedation‐related adverse events. We sought to examine the association between timing of opioids and the incidence of adverse sedation outcomes. Methods: We conducted a secondary analysis of a prospective cohort of children aged 0 to 18 years who received sedation for a painful procedure in six Canadian pediatric EDs from July 2010 to February 2015. The primary risk factor was timing of opioid administration, adjusted for age, opioid type, preprocedural and sedation medications, and procedure type. Outcomes were 1) oxygen desaturation, 2) vomiting, and 3) positive pressure ventilation (PPV). Results: Of the 6, 295 children in the original cohort, 1, 806 (29%) received a preprocedural opioid. Patients receiving preprocedural opioids had a higher incidence of oxygen desaturation (risk difference = 4.3%, 95% confidence interval [CI] = 2.9% to 5.8%), vomiting (risk difference 2.0%, 95% CI = 0.7% to 3.3%), and PPV (risk difference = 1.5%, 95% CI = 0.7% to 2.3%). Multivariable regression with timing of opioids modeled as a restricted cubic spline revealed the risk for each outcome was highest when opioids were administered in the 30 minutes prior to sedation. Timing of opioid administration was statistically significantly associated with oxygen desaturation and vomiting (p < 0.0001) but not with PPV (p = 0.113). Conclusions: Timing of opioids was significantly associated with the risk of oxygen desaturation and vomiting. Being aware of this increased risk will help clinicians prepare for sedation and the potential need for patient rescue.